Tissue engineering and regenerative medicine research and development in Malaysia: A scientometric study based on relevant conferences from 2004 to 2014 - Mohd. Azharuddin, Nur Syamimi; Ahmad Radzi, Muhammad Aa’zamuddin; Sha'ban, Munirah (IPPT, USM,TESMA, MSCRT, 2016)
Purpose: To examine the trend of tissue engineering and regenerative medicine (TERM) research progress. The study aims to fill the gap of literature dearth that systematically addresses the trend of TERM research and development in Malaysia. Methods: A scientometric study of published abstracts presented in International Conference on Biomaterials and Tissue Engineering 2004, National Tissue Engineering and Regenerative Medicine Scientific Meeting 2006 and Malaysian Tissue Engineering and Regenerative Medicine Scientific Meeting 2008-2014 was conducted. The study explored the publication productivity trends, authorship productivity, collaboration pattern, sources of funding and areas of interest. These data were examined in relation to the overall publications. Results: A total of 362 abstracts were published in 6 conferences from 2004 to 2014. Majority of publications were multi-authored involving public institutions of higher learning. The collaborations between local and international authors were noted. The active research areas and themes were identified. It can be appreciated that the conference participation expands with the coefficient of determination of R2 = 0.0775. Thus, Malaysian researchers seemed to be focusing on various cell sources, biomaterials, signaling factors and organ systems. A declining trend in these areas of interest is observed. Based on the study, certain prominent researchers and institutions are actively upholding the TERM research. Conclusion: The present study is hoped to shed some lights and serves as a reference towards the advancement of TERM research in Malaysia.